Adaptive potential of winter durum wheat varieties according to the trait ‘1000-seed weight’ - O. A. Dubinina; N. E. Samofalova; N. N. Vozhzhova (Зерновое хозяйство России, 2018)
The article gives the assessment and evaluation of ten winter durum wheat varieties according to the trait ‘1000-seed weight’. There has been shown the stability and adaptability of the varieties to the conditions of the Rostov region, whose soil-climatic conditions are favourable for winter durum wheat cultivation. The variety ‘Donskoy yantar’ turned to be less varying in the trait ‘1000-seed weight’ (V = 2.7 %) and it was less adaptive to the environment among the rest of the varieties (bi = 4.68). The maximum weight of 1000-seed during the years of study showed the variety ‘Lazurit’ (48.0g). The most adaptable varieties with a good response to the change of the environment are the varieties ‘Oniks’ (bi = 6.16), ‘Agat donskoy’ (bi = 6.23) and ‘Lazurit’ (bi =6.63). The best varieties with the highest value of the trait ‘1000-seed weight’ under various growing conditions are the varieties ‘Lazurit’ and ‘Amazonka’.